Vertu: Rise and Fall of the Ultimate Luxury Mobile Phone - Donnelly, Brandon (Journal of Marketing Development and Competitiveness, 2020)
Vertu was initially founded in 1998 by Nokia and Frank Nuovo, designing premium cell phones with bold designs at absolute luxury prices. Like luxury timepiece business, Vertu focused on design quality, creating a distinct, bold looking mobile handset with premium materials for high net worth individuals. The organization suffered immense setbacks after several acquisitions and an inability to adjust to the growing shifts in the technology market, forcing bankruptcy, until a restructure and focus on the APAC market. The paper focuses on the overreliance on Nokia technology and systemic failure to radically innovate and an old business led to collapse.